Air pollution and asthma. - Barnes, P. J. (BMJ Group, 1994)
The role of air pollution in the increased prevalence and morbidity of asthma has been widely debated, but results to date indicate that the normally encountered levels of air pollution are unlikely to contribute to a worsening of asthma. When the levels of sulphur dioxide (SO2) are exceptionally high it is possible that asthmatic patients may have increased symptoms after exertion, since this irritant gas acts as a trigger to bronchoconstriction. There is also evidence that suspended particles may also act as an inciter of asthma symptoms when concentrations are high. Experimentally, ozone in high concentrations may increase airway responsiveness in both normal and asthmatic subjects by inducing airway inflammation, but asthmatic individuals show the same responses as normal subjects and there is little or no evidence to link increases in ambient ozone with an increase in asthma. There is little evidence that nitrogen dioxide (NO2), even at the peak levels recorded, has any significant effect on airway function in normal or asthmatic individuals. Other air pollutants which are present in lower concentrations have not been studied as extensively, but there is no convincing evidence that they cause significant respiratory symptoms in asthmatic patients. It is still possible that combinations of air pollutants may have greater effects on airway function than exposure to a single pollutant, although there is little evidence to support this. Epidemiological evidence provides little support for the idea that atmospheric pollution levels are related to the frequency of asthma symptoms or the frequency of attacks. More importantly, there is no evidence that asthma prevalence or aetiology is related to the level of air pollution. A review of currently available information therefore provides little evidence for the widely expressed view that atmospheric pollution is related to increased prevalence or morbidity of asthma or is related to the causation of asthma.